“No female weakness harbour’d there”: Epic Reframing of the Notorious Queen in Margaret Holford’s Margaret of Anjou: A Poem - Okaycan Dürükoğlu (Ideas: Journal of English Literary Studies)
Margaret Holford was a Romantic woman poet who published all of her works in the early nineteenth century. At the end of her literary career, she wrote her final work Margaret of Anjou: A Poem (1816). The poem retells the story of Margaret of Anjou’s fight for her son’s legitimacy for the English crown. Margaret of Anjou was the wife of Henry VI of England and she has always been regarded as one of the most bloodthirsty queens of England as a result of her decisions and actions in the Wars of the Roses. Although the Queen had a notorious reputation for centuries, Holford did not contribute to this negative image of her and she attributed positive qualities to Queen Margaret’s character by tailoring her as an epic hero. By writing in a heroic mode and attributing epic characteristics to her poem, Margaret Holford transgresses the boundaries of the epic genre in which masculine ideals and goals are celebrated in general. Holford reacts to the male-centred epic genre with her female epic hero. Accordingly, this study focuses on how Holford fashions Margaret of Anjou as an epic hero, and how she subverts the traditional epic tradition with her female heroine.